Economic potential and environmental impact of metal recovery from copper slag flotation tailings - BAŞYİĞİT, MİKAİL; UZUN KART, ELİF (My University, 2023)
© 2022 Elsevier LtdCopper slag has long been the subject of metal recovery. However, it has become apparent that copper slag flotation tailings can meet resource requirements under certain circumstances. Besides copper, zinc and cobalt can also be obtained from slag tailings. This study investigated the potential of copper slag tailings alongside global metal supply and demand dynamics. It has been emphasized that, such as copper slag, slag tailings can be a new potential resource for global base metals, considering global and domestic copper production, consumption, and base metal prices. In addition, its economic and environmental sustainability was evaluated from a waste management perspective.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; İktisat; Hukuk; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Economics; Law; Sosyal Bilimler (SOC); Ekonomi ve İş; Sosyal Bilimler Genel; EKONOMİ; SOSYOLOJİ; ÇEVRE ÇALIŞMALARI; HUKUK; Social Sciences (SOC); ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; ECONOMICS; SOCIOLOGY; ENVIRONMENTAL STUDIES; LAW; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Ekonomi ve Ekonometri; Yönetim, İzleme, Politika ve Hukuk; Fizik Bilimleri; Sociology and Political Science; Social Sciences & Humanities; Economics and Econometrics; Management, Monitoring, Policy and Law; Physical Sciences; Base metals; Copper slag; Copper slag flotation tailings; Economic potential; Environmental impact; Sustainability; Waste management